PROBLEMATIKA PEMBELAJARAN HAFALAN SURAT-SURAT PENDEK DI RA. PERWANIDA SEMINGKIR DESA KALICUPAK KIDUL KECAMATAN KALIBAGOR KABUPATEN BANYUMAS - Mar'atun Sholihah (Jurnal Penelitian Agama, 2018)
Abstract: The results of this study that learning to memorize short letters in RA. Perwanida Semirir Kalicupak Kidul Village, Kalibagor Subdistrict, Banyumas Regency, namely: (a) The ability of teachers and mastery of memorization material for short letters is sufficient but still needs to be improved because to obtain better learning outcomes besides there are some shortcomings that can be found. (b) The methods used in the delivery of material need to be made more varied. (c) The use of media in the process of teaching and learning activities, especially memorizing short letters is very necessary and needs to be held or prepared. (d) Evaluation of memorizing short letters that have been implemented needs to be intensified. (e) Lack of support and attention from parents for memorizing short letters from the teacher. Key words: memorizing short letters, and problems.